Accelerating Lithium Deposition Kinetics Via Lithiophilic Ag-Decorated Graphitic Carbon Nitride Spheres for Stable Lithium Metal Anode - Lim, Hyojun; Choi, Minsu; Kang, Haeun; Choi, Wonchang (WILEY, 2025)
This study presents a novel Li metal host material with a unique hollow nano-spherical structure that incorporates Ag nano-seeds into a graphitic carbon nitride (g-C3N4) shell layer, referred to as g-C3N4@Ag hollow spheres. The g-C3N4@Ag spheres provide a managed internal site for Li metal encapsulation and promote stable Li plating. The g-C3N4 spheres are uniformly coated using polydopamine, which has an adhesive nature, to enhance lithium plating/stripping stability. The strategic presence of Ag nano-seeds eliminates the nucleation barrier, properly directing Li growth within the hollow spheres. This design facilitates highly reversible and consistent lithium deposition, offering a promising direction for the production of high-performance lithium metal anodes. These well-designed g-C3N4@Ag hollow spheres ensure stable Li plating/stripping kinetics over more than 500 cycles with a high coulombic efficiency of over 97%. Furthermore, a full cell made using LiNi0.90Co0.07Mn0.03O2 and Li-g-C3N4@Ag host electrodes demonstrated highly competitive performance over 200 cycles, providing a guide for the implementation of this technology in advanced lithium metal batteries. The g-C3N4@Ag as a lithium metal host was prepared by a simple synthesis method. The g-C3N4@Ag is composed of a hollow sphere with Ag nano-seeds in a g-C3N4 shell. The g-C3N4@Ag hollow spheres ensure stable Li plating/stripping kinetics. The full-cell using NCM cathode and Li-g-C3N4@Ag anode showed highly competitive performance over 200 cycles. image